Fishery buy back programmes and economic welfare - Campbell, Harry F. (Australian Journal of Agricultural Economics, 1989)
Fishery buy‐back programmes reduce the availability to the industry of certain inputs used in the harvesting process, thereby increasing fishing costs and reducing the amount of effort applied to the fishery. The reduction in effort generates an economic benefit which must be weighed against the increased costs. The paper develops an economic model of a buy‐back programme which can be used to estimate the effect of the programme on economic welfare. The model is applied to the Tasmanian rock lobster fishery.